Ethical evaluation of Daniel A. Carrion's autoexperimentation and his personality profile - Perales, Alberto (2003)
Objectives: 1) Ethical analysis of Daniel A Carrion’s (DAC) autoexperimentation taking as a variable his personality profile; 2) To evaluate the ethical dilemma publicly raised on October 6 of 1885 by Dr. Ignacio La Puente, at that time, the Faculty of Medicine’s Secretary. Material and method: 1) Qualitative classification of documents; 2) Classification of sources of references according to their origint; 3)Organization of a systematic chronological register; 4) Critical analysis of the classified documents and identification of DAC’s specific behavior characteristics; 5)Construction of his personality profile by identifying his behavioral response patterns by criteria of coherence, interdependency with the situational context, unicity and interrelation with the local and international context of his time; 6) Comparison of DAC’s personality profile with the basic qualifications that make a scientist or a good researcher described by Selye. Results and conclusions: Of the final twelve conclusions the following are summarized: 1º DAC’s personality shows normal traits without evidence of neuroticism or psychopathy: 2º In his character traits stand out his assertiveness, perseverance, discipline, emotional stability, honesty with himself and others, good interpersonal relationships, leadership capacity and strong conviction on his knowledge; 3º His life was entirely devoted to science; 4º The thesis of the accidental death of his father is false. He died in 1877, in Loja (Ecuador). There is no evidence that DAC knew this fact; 7º Graphological analysis confirms the identified personality profile; 8º DCA’s personality profile fulfills all Selye’s criteria; 9º His autoexperimentation supports itself on a solid scientific formulation and a high moral values scale in which stand out an elevated level of beneficence and an extreme attachment to truth; 11º DCA’s autoexperimentation fulfills all research ethical principles 12º Dr. La Puente’s accusation is shown to be totally unsupported.